Who Watches the Trustee? Rethinking Bankruptcy Trustee Liability in Ukraine and Worldwide - Boiarchukov, Serhii G.; Zinevych, Oleksandr L.; Dei, Maryna О.; Dei, Herasym; Anisimov, Kyrylo (Theoretical and Practical Research in Economic Fields; Vol 17 No 2 (2026): TPREF Volume XVII Issue 2(38) June 2026, 2026)
This paper examines the legal processes that can be applied to the liability of bankruptcy of trustees in international practice. It is relevant because it is necessary to protect the rights of the parties on insolvency procedures, increase transparency, avoid abuse, and align the Ukrainian legislation with the international standards. A comparative legal approach is used to analyze the regulation of the liability of bankruptcy trustees in the USA, Germany, France, Sweden and the UK. The research is found on law, case law and scholarly studies. The comparison is conducted based on the main criteria: the qualification criteria, supervision, civil and criminal liability, insurance and disciplinary measures. Four primary types of liability were outlined, and they include administrative, judicial, self-regulatory and hybrid. They are both good and bad in their respects of accountability, effectiveness and transparency. The most balanced is the hybrid model, which combines state supervision, judicial oversight and professional self-regulation. A multi-tiered accountability system is proposed, comprising institutional, judicial, professional, financial and digital components. Effective accountability for bankruptcy trustees is achieved through the interaction of various control mechanisms, rather than within a single model. The proposed hybrid concept promotes greater transparency and trust in the bankruptcy system and can be used to improve Ukrainian legislation in line with international standards.